Rancang Bangun Aplikasi Mobile Game Edukasi Ilmu Pengetahuan Alam Untuk Anak Kelas VI Sekolah Dasar - Siswanto, Yogi; Purnama, Bambang Eka; ., Sukadi (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
ABSTRACTÂ Â Â : Growth of game in fast world progressively, do not aside from in Indonesia. Game in this time have become entertainment amusement alternative to is old, young, woman and also man. Target of making a game for example education. This Game will be more be majored to support study process with concept